Musculoskeletal symptoms and ergonomic hazards among room attendants in hotel industries - Abdol Rahman, Mohd Nasrull; Muhamad Jaffar, Mohd Syahir (Human factors and Ergonomics Society Malaysia (HFEM), 2017)
Ergonomic hazards which contribute to Musculoskeletal Disorders (MSDs) among room attendants were considered as a problem or trouble since these ergonomic problems would affect their work performance for hotel industries. Data for MSDs prevalence among room attendants were collected using Nordic Musculoskeletal Questionnaire (NMQ) and direct observation via Washington Industrial Safety and Health Act (WISHA) Checklist for examining the ergonomic hazards at hotel industries. The highest body part trouble among room attendants in the last 12 months were low back pain (60%), followed by wrists/hands (41.5%), and knees (36.9%). WISHA Checklist results showed that most of room attendants were found in hazard level for risk factors involving awkward posture and highly repetitive motion. All the results obtained showed that the essential ergonomic interventions are needed to eliminate risk of exposures to MSDs among room attendants.